Low carbon and economic dispatching of electric-gas integrated energy system with liquid storage carbon capture equipment - Hu, Yang; Tang, Ye; Wang, Kaiyan; Yang, Xiaoping (Frontiers in Energy Research, 2022)
Because of the coupling of CO2 absorption and treatment, conventional carbon capture power plants lack the flexibility of power plant operation. This paper provides a liquid storage carbon capture power plant(LSCCPP) with solution storage, analyzes the "energy time-shift" features of the solution storage, and creates a joint operating model of the LSCCPP and Power to Gas(P2G) based on this. Taking into account the carbon market trading mechanism, this paper develops a low-carbon economic dispatch model for an integrated electric-gas energy system with the LSCCPP, with the goal of achieving the lowest overall system cost. Moreover, the proposed dispatch model is solved by transforming the model into a mixed-integer linear programing problem and calling CPLEX. Finally, a modified example system is used to demonstrate the validity of the proposed model. The results show that the suggested low-carbon dispatch model has a significant reference for enhancing the system's use of wind power and accomplishing the low-carbon efficient functioning of the integrated electric-gas energy system.